2022
DOI: 10.14202/vetworld.2022.1557-1565
|View full text |Cite
|
Sign up to set email alerts
|

First report of multidrug-resistant Salmonella Infantis in broiler litter in Tolima, Colombia

Abstract: Background and Aim: Salmonella has been identified as one of the most widely distributed zoonotic pathogens in broiler litter. Multidrug-resistant strains have been isolated from salmonellosis outbreaks, compromising the success of their treatment. This study aimed to isolate and identify Salmonella spp. serovars in healthy broiler litter in Tolima (Colombia), determine their resistance to different antimicrobials, and detect genes associated with β-lactam resistance that could be useful to control Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Our ampicillin data differ from those reported by Hawkey et al [58], who detected the blaTEM gene in 18% of human-derived Salmonella isolates resistant to this antibiotic, our study found no blaTEM gene presence. Similarly, Salmonella isolates resistant to cefotaxime from broiler litter samples were blaTEM-negative [71]. Nonetheless, the blaTEM gene was present in 79.2% and the tetA gene in 75% of Salmonella isolates from sulfonamide-treated diarrheic calves [72].…”
Section: Discussionmentioning
confidence: 99%
“…Our ampicillin data differ from those reported by Hawkey et al [58], who detected the blaTEM gene in 18% of human-derived Salmonella isolates resistant to this antibiotic, our study found no blaTEM gene presence. Similarly, Salmonella isolates resistant to cefotaxime from broiler litter samples were blaTEM-negative [71]. Nonetheless, the blaTEM gene was present in 79.2% and the tetA gene in 75% of Salmonella isolates from sulfonamide-treated diarrheic calves [72].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that antimicrobials may be being misused in small, and medium sized broiler farms. Hence, broiler chicken litter should be monitored routinely to lessen these bacteria from spreading [7]. In commercial broiler production, antibiotics are routinely administered at low doses for disease prevention and growth promotion [8].…”
Section: A Direct Land Applicationmentioning
confidence: 99%